(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Green computing is a low-cost, high-efficiency strategy to developing, producing, and utilizing computers and computer-related goods that conserves natural resources while reducing negative environmental impacts. In today’s culture, businesses are always seeking for ways to conduct their operations in an ecologically sustainable manner. As the popularity of computers rose, almost every industry felt it vital to include computers into their operations. They’ve also made things a lot easier to deal with and organize. Almost every firm relies on technology to achieve its goals. Many of the elements that make up your IT are dangerous. It includes harmful elements like as lead, hexavalent chromium, and mercury, which are all toxic when discarded in landfills. This paper debates the significance of green computing and why it is necessary in today’s environment. It also walks you through how to put Green computing into reality. This paper also discusses some fundamental ways for dramatically reducing the environmental impact of computers. On upcoming days green computing attempts to limit the use of harmful chemicals, boost energy efficiency, as well as encourage the biodegradability or recyclability of obsolete items and industrial waste